Prognostic Value of Circulating Tumor Cells in Ovarian Cancer: A Meta-Analysis - Zhou, Yunlan (PLoS One, 2015)
BACKGROUND: The prognostic value of circulating tumor cells (CTCs) in ovarian cancer has been investigated in previous studies, but the results are controversial. Therefore we performed a meta-analysis to systematically review these data and evaluate the value of CTCs in ovarian cancer. MATERIALS AND METHODS: A literary search for relevant studies was performed on Embase, Medline and Web of Science databases. Then pooled hazard ratios (HRs) for survival with 95% confidence intervals (CIs), subgroup analyses, sensitivity analyses, meta-regression analyses and publication bias were conducted. RESULTS: This meta-analysis is based on 11 publications and comprises a total of 1129 patients. The prognostic value of the CTC status was significant in overall survival (OS) (HR, 1.61;95% CI,1.22–2.13) and progression-free survival (PFS)/disease-free survival (DFS) (HR, 1.44; 95%CI, 1.18–1.75). Furthermore, subgroup analysis revealed that the value of CTC status in OS was significant in "RT-PCR" subgroup (HR, 2.02; 95% CI, 1.34–3.03), whereas it was not significant in "CellSearch" subgroup (HR, 1.15; 95% CI 0.45–2.92) and "other ICC" subgroup (HR, 1.09; 95% CI 0.62–1.90). The presence of CTC was also associated with an increased CA-125 (OR, 4.07; 95%CI, 1.87–8.85). CONCLUSION: Our study demonstrates that CTC status is associated with OS and PFS/DFS in ovarian cancer.